2021
DOI: 10.46827/ejefr.v5i2.1155
|View full text |Cite
|
Sign up to set email alerts
|

Population Growth Induced and Households Financial Vulnerability in Nigeria

Abstract: Nigeria has been recording a rapid increase in its population over the years. This reality has posed a serious concern for the welfare of households especially as the increase in population growth puts households at the risk of financial vulnerability. Based on this, this study is on the move to examined the impact population growth induced has on household in Nigeria. The study made use of secondary data obtained from World Bank and the Central Bank statistical bulletine spanning from 1981 to 2020 to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Previous studies have reported a reciprocal relationship between financial deepening and growth in the manufacturing sector. This is exemplified by the research conducted by Mbah and Okoli (2020).…”
Section: Relationship Between Financial Deepening and The Growth Of T...mentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies have reported a reciprocal relationship between financial deepening and growth in the manufacturing sector. This is exemplified by the research conducted by Mbah and Okoli (2020).…”
Section: Relationship Between Financial Deepening and The Growth Of T...mentioning
confidence: 93%
“…Manufacturing's contribution to national economies has been extensively documented (Kayodeo, Ibenta, & Owoputi, 2020;Mbah & Okoli, 2020), and this fact is generally accepted. According to Aiginger and Rodrik's (2020) research, there is widespread agreement that the manufacturing sector is essential to national economic progress.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation